Recent Advances in Cyclization Reactions of 1,5-Enynones and 1,6-Enynones - Rajai-daryasaraei, Saideh; Fathi Vavsari, Vaezeh; Jamshidi, Elmira; Balalaie, Saeed (Synlett)
The alkyne functional group and α,β-unsaturated carbonyl compounds serve as key building blocks for assembling fused aromatic and heterocyclic structures. The placement of these two functional groups at the ortho positions on a benzene ring provides an opportunity to design diverse reactions and access a wide variety of aromatic compounds. By using appropriate catalysts, radical initiators, nucleophiles, or electrochemical circumstances, the selectivity and specificity of the reaction can be precisely controlled, leading to the formation of C-C and C-heteroatom bonds and selective cyclization. Various organic scaffolds, including indenones, benzofurans, naphthoquinones, benzofluorenones, and isochromenes, can be efficiently produced through these transformations.This review provides readers with a detailed understanding of how catalysts and reaction circumstances affect the regio-and stereoselectivity of ynenone reactions, enabling them to choose the best reaction routes.